A questionnaire-based survey methodology for systematically validating goal-oriented models. Issue 2 (June 2016) - Hassine, Jameleddine; Amyot, Daniel
Abstract Goal models represent interests, intentions, and strategies of different stakeholders. Reasoning about the goals of a system unavoidably involves the transformation of unclear stakeholder requirements into goal-oriented models. The ability to validate goal models would support the early detection of unclear requirements, ambiguities, and conflicts. In this paper, we propose a novel validation approach based on the Goal-oriented Requirement Language (GRL) to check the correctness of GRL goal models through statistical analyses of data collected from generated questionnaires. System stakeholders (e.g., customers, shareholders, and managers) may have different objectives, interests, and priorities. Stakeholder conflicts arise when the needs of some group of stakeholder compromise the expectations of some other group(s) of stakeholders. Our proposed approach allows for early detection of potential conflicts amongst intervening stakeholders of the system. In order to illustrate and demonstrate the feasibility of the approach, we apply it to a case study of a GRL model describing the fostering of the relationship between the university and its alumni. The approach brings unique benefits over the state of the art and is complementary to existing validation approaches.